2019
DOI: 10.1371/journal.pone.0209670
|View full text |Cite
|
Sign up to set email alerts
|

Children and adults successfully comprehend subject-only sentences online

Abstract: In many offline studies, children show selectively better comprehension of sentences with the focus particle only when it modifies the object argument (Jane only ate an apple) than they do when it modifies the subject argument (Only Jane ate an apple). Here we explore the nature of this asymmetry by examining performance in a different kind of task: the moment-to-moment comprehension of unambiguous sentences. If past errors reflect a fundamental difference in representation or complexity of computation, we wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The 5-year-old children showed more difficulty in understanding pre-subject focus sentences, while the 6-year-old children had basically mastered the pre-subject focus sentences [16]. This result confirmed that the age between 5 and 6 years old is important for cognitive development regarding focus structures [11,15]. Nevertheless, the aforementioned research solely examined the eye movement processing characteristics of Chinese children's comprehension of focus structures, without delving into specific cognitive factors.…”
Section: Cognitive Factors Affecting the Understanding Of Chinese Foc...mentioning
confidence: 58%
See 3 more Smart Citations
“…The 5-year-old children showed more difficulty in understanding pre-subject focus sentences, while the 6-year-old children had basically mastered the pre-subject focus sentences [16]. This result confirmed that the age between 5 and 6 years old is important for cognitive development regarding focus structures [11,15]. Nevertheless, the aforementioned research solely examined the eye movement processing characteristics of Chinese children's comprehension of focus structures, without delving into specific cognitive factors.…”
Section: Cognitive Factors Affecting the Understanding Of Chinese Foc...mentioning
confidence: 58%
“…Inhibitory control is a subcomponent of executive function. Another perspective is that although children can understand both types of focus structures as quickly as adults, their cognitive flexibility leads to them having difficulty switching between the two types of sentences in the same experimental sequence, leading to interference effects [11]. Cognitive flexibility is another subcomponent of executive function.…”
Section: Cognitive Factors Affecting the Understanding Of Chinese Foc...mentioning
confidence: 99%
See 2 more Smart Citations
“…Experiment 1: visual-world task Experiment 1 comprised two linked experiments focused on the phonemic cohort competition effect. This effect is well-suited for testing the efficacy of web-based visualworld eye-tracking, as it has been replicated many times with both adults (e.g., Allopenna et al, 1998;Dahan & Gaskell, 2007;Dahan et al, 2001;Farris-Trimble & McMurray, 2013;Magnuson et al, 1999;inter alia) and children (e.g., Desroches et al, 2006;Sekerina & Brooks, 2007;Rigler et al, 2015;Weighall et al, 2017;inter alia), and the presence of cohort activation is often used to investigate higher-level linguistic constraints on incremental language processing (e.g., Dahan & Tanenhaus, 2004;Gaston et al, 2020;Ito et al, 2018;Li et al, 2022;Paul et al, 2019). In a visual-world context, cohort competition effects arise when listeners hear a target word that shares onset phonemes with one of the images on the screen; when hearing the onset of the target word (e.g., beaker), listeners fixate more on the image of a cohort competitor (e.g., beetle) than phonologically-unrelated distractors (e.g., carriage) (e.g., Allopenna et al, 1998).…”
Section: Introductionmentioning
confidence: 99%